Invisible and Unbound? The Challenge and Practice of Evaluating Embedded Facilitation. Issue 149 (March 2016) - Dart, Jessica; Roberts, Megan
Abstract: With the movement in Australia toward smaller government, there is a growing emphasis on how to allocate scarce resources efficiently. In this tighter financial climate, placement of facilitators into programs and services offers a promise of achieving more with less. As a result there are a plethora of government and nongovernment programs that make use of facilitators directly funded by programs. Despite the appeal of using facilitators, little attention has been paid to how best to evaluate the facilitation component of programs. The literature on the nature of facilitation points to difficulties in attributing outcomes to facilitation and the importance of understanding the intent. We use a case study of the past 15 years of evaluating Landcare programs in Australia to explore the challenges further and offer practical ideas for any evaluators faced with the prospect of evaluating a program that has a facilitative element.